2009
DOI: 10.1371/journal.pone.0008199
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutations in Primary Colorectal Cancer Tumors and Related Metastases: A Potential Role in Prediction of Lung Metastasis

Abstract: Background KRAS mutations in colorectal cancer primary tumors predict resistance to anti-Epidermal Growth Factor Receptor (EGFR) monoclonal antibody therapy in patients with metastatic colorectal cancer, and thus represent a true indicator of EGFR pathway activation status.Methodology/Principal Findings KRAS mutations were retrospectively studied using polymerase chain reactions and subsequent sequencing of codons 12 and 13 (exon 2) in 110 patients with metastatic colorectal tumors. These studies were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
136
1
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(150 citation statements)
references
References 22 publications
9
136
1
4
Order By: Relevance
“…Second, KRAS status was obtained from routinely available archival material and does not incorporate potential discordance in KRAS status between a primary tumour and its metastases. However, KRAS mutations are thought to be highly concordant during the progression of the disease (Artale et al, 2008;EtienneGrimaldi et al, 2008;Santini et al, 2008;Cejas et al, 2009). Third, the traditional sequencing (Sanger) method (with B20% allele frequency as lowest threshold for detection) or a mass spectroscopy method (B15% allele frequency) for detection of KRAS mutations was used, both of which have lower sensitivity for mutation analysis than current next-generation sequencing approaches (B5% allele frequency; Jimeno et al, 2009;Plesec and Hunt, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Second, KRAS status was obtained from routinely available archival material and does not incorporate potential discordance in KRAS status between a primary tumour and its metastases. However, KRAS mutations are thought to be highly concordant during the progression of the disease (Artale et al, 2008;EtienneGrimaldi et al, 2008;Santini et al, 2008;Cejas et al, 2009). Third, the traditional sequencing (Sanger) method (with B20% allele frequency as lowest threshold for detection) or a mass spectroscopy method (B15% allele frequency) for detection of KRAS mutations was used, both of which have lower sensitivity for mutation analysis than current next-generation sequencing approaches (B5% allele frequency; Jimeno et al, 2009;Plesec and Hunt, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This might be relevant in patients who have already received chemotherapy, because tumor cells may be sparse in these cases. However, four of the 12 studies using sequencing mentioned that the samples tested in their study had to contain Ն70% tumor cells [28,45,47,54]. All four of them reported discordance in some cases.…”
Section: Discussionmentioning
confidence: 99%
“…2 Since then, KRAS genotyping has become routine practice in many departments of surgical pathology; often, any available tumor-bearing sample is used for genotyping. This includes samples from the primary tumor, 18,19 particularly when a biopsy is not performed on liver metastases detected by computed tomographic scan. However, evidence is increasing that the KRAS mutational status is heterogeneous and no recommendations are made regarding which tumor should be tested (eg, primary tumor or liver metastasis).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, testing of any primary tumor sample, as is often routinely performed in surgical pathology departments, may produce misleading results in many patients. 18,19 Likewise, attention must be given to studies in which discrepancies were observed between primary tumors and liver metastases. Although a de novo mutation is one putative explanation, a metachronous secondary CRC is another explanation.…”
Section: /Brafmentioning
confidence: 99%